KETAHANAN PANGAN BERBASIS DIVERSIFIKASI PANGAN UNTUK KEBERLANJUTAN EKONOMI: ANALISIS BIBLIOMETRIK - Muhamad Abien Pratama; Artika Sari Devi; Dewi Rohma Wati; Dzikri Adiathoriq (Jurusan Penyuluhan Pertanian FP UHO, 2026)
Food security is a strategic global issue directly linked to human basic needs, social stability, and national economic sustainability. As an agrarian country, Indonesia faces major challenges due to its heavy dependence on rice as a staple food, which increases the vulnerability of the national food system. Food diversification has therefore become a key strategy to strengthen food security and economic sustainability by utilizing local food resources such as cassava, corn, sago, and tubers. This study employs a quantitative bibliometric analysis approach to map the development of research on food diversification and food security in Indonesia during the 2010–2024 period. Data were collected from Google Scholar, limited to relevant scientific articles indexed in SINTA, then exported in RIS format, curated using Mendeley, and analyzed through VOSviewer 1.6.20. The analysis covered publication trends, author collaboration networks, keyword co-occurrence, and thematic relationships. The results show a significant increase in publication output and citation performance over the past three decades, with an average of 11.35 citations per article and an H-index of 63, indicating a strong academic influence in this research domain. Keyword network visualization reveals that the most frequently studied themes include household food security, consumption diversification, local food innovation, and agricultural development strategies. Overall, this study demonstrates that research on food security based on food diversification in Indonesia is multidisciplinary and increasingly application-oriented, highlighting its growing role in strengthening local economies and informing sustainable food policy formulationl.